PERAN DINAS PENDIDIKAN TERHADAP PEMANTAUAN EFEKTIVITAS PELAKSANAAN KAWASAN TANPA ROKOK DI LINGKUNGAN SEKOLAH KOTA DENPASAR - Ni Putu Raisa Prita Loka; Made Gde Subha Karma Resen (Kertha Negara : Journal Ilmu Hukum, 2023)
Non-Smoking Areas in Denpasar City’s schools environment are regulated based on Regulation of the Minister of Education and Culture of the Republic of Indonesia (Permendikbud) Number 64 of 2015 and Regional Regulation of Denpasar City Number 7 of 2013. The formulation of the problems from this research are: the legal basis for developing a Non-Smoking Areas, especially in the Denpasar City’s schools environment and how is the role of the Department of Education in the monitoring the effectiveness of Non-Smoking Areas Implementation, especially in Denpasar City’s schools environment. The needs for a legal umbrella related Non-Smoking Areas in Denpasar City’s schools environment is a legal obligation for the state, in this case, the central government and local governments to create legal protection for community and individuals from the dangers of exposure to cigarette smoke on health and the fulfillment of everyone's human rights to a clean environment, healthy and free from exposure of cigarette smoke. Efforts that can be done by the schools and the Denpasar City’s Department of Education, Youth and Sports in implementing the effectiveness of the Non-Smoking Areas in school environment are in the form of enforcing rules, monitoring, and imposing sanctions for violators of the Non-Smoking Areas in the Denpasar City’s schools environment.